Weighted Scoring Design for ART Healthcare Centre - Devarakonda, Shiva; Vaghela, Arjunsinh; Chudasama, Jalpaba (Frontiers on Healthcare Research, 2025)
Background: Antiretroviral Therapy (ART) centers are critical in providing medical, psychological, and social support to People Living with HIV (PLHIV), as per the National AIDS Control Organization (NACO) guidelines. However, many ART centers in India face infrastructural inefficiencies, including overcrowding, poor ventilation, inadequate sanitation, and non-compliance with updated regulations. The existing layout of a long-operational ART center, established in 2008, has demonstrated such inefficiencies, necessitating a strategic redesign to optimize operational flow and improve patient outcomes. Methods: This study employed a weighted scoring system to evaluate and compare three proposed layout alternatives against the existing design. The methodology included activity flowchart mapping, space utilization studies, stakeholder input, and multi-criteria decision analysis. Twelve design evaluation criteria were prioritized using weighted scores, including feasibility (11%), patient safety (10.5%), workflow efficiency (10%), and objective adherence (13%). Designs were assessed for spatial efficiency, safety, robustness, usability, and environmental impact. Results: Design 3 achieved the highest weighted score of 6.91, outperforming Design 2 (6.865), Design 1 (5.645), and the original layout (5.275). The optimal layout improved patient flow, integrated dedicated counseling areas, enhanced staff workspaces, and improved sanitation and ventilation. Correlation analyses highlighted critical interdependencies and trade-offs among feasibility, safety, and cost factors. Design 3 also demonstrated a 30–40% reduction in congestion, compliance with NACO standards, and enhanced operational efficiency. Conclusion: The weighted scoring methodology effectively identified the optimal ART center layout. Design 3 significantly improved spatial organization, privacy, hygiene, and workflow. Future work could incorporate IoT-based monitoring and AI-driven real-time optimization for adaptive facility management. This model can be extended to other healthcare infrastructure redesigns to enhance quality and compliance.